PENGARUH PEMBELAJARAN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. HUTAHEAN PEKANBARU - Srimulatsih, Mahbubah (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This research was conducted at PT.HUTAHEAN Pekanbaru. The purpose of this research is to determine the effect of organizational learning on employee performance. The population inthis research is 52 employees. The data used are primary data and secondary data. This research used quantitative method and analyzed by simple linear regression. The result showed that the organizational learning has positive effect on employee performance.